Development of a productivity index for engineering schools using multiattribute analysis - Castillo, Aura Villegas (1989)
The measurement of productivity of education systems necessarily rely on numerous interrelated aspects and judgements. This paper illustrates an application of the concepts of multi-attribute utility evaluation of productivity for engineering educational institutions based on the assessment of deans of engineering schools/colleges in the Philippines. The school administrators selected for the surveys and elicitation process were from school that offered at least two of the four major engineering baccalaureate programs. These are, B.S. Chemical Engineering, B.S. Civil Engineering, B.S. Electrical Engineering, B.S. Mechanical Engineering. Sixty-eight schools were selected from the total list of recognized schools (based on the official list of recognized engineering schools as of 1987, Technical Panel for Engineering Education) as prospective respondents. Two surveys were conducted. The first survey was aimed at identifying the major concerns or that were considered to be measures of the educational productivity of school, determining their respective ranks and relative importance. The second survey was conducted to determined the range of values of the identified concerns from the initial survey, assess their utility functions and scaling constants. Only 15 responded to the first survey and only 5 out of the 15 responded to the second survey. Seventeen measures of productivity were identified: Cost efficiency, completion rate, percentage of honor graduates, board examination passing percentage, board examination competitiveness, probability of employment, probability of engineering employment, quality and quantity of research outputs expressed in terms of number of completed research projects and number of research projects with impact, Number of published books, number of articles/ technical papers written, number of technical papers presented, number of technical lectures delivered, number of sponsored seminars, number of consultancy projects, faculty research involvement, faculty publication involvement, and faculty consultancy involvement. The assessment produced an additive multi-attribute function with a bi-linear submodel for quality and quantity of research outputs. The model was tested using 4 engineering schools in the National Capital Region. Information regarding productivity measures were kindly provided by the respective school administrators and the Technical Panel for Engineering Education Research and Development Group. The model was partially successful in evaluating the performance of the selected schools. The potential application of the resulting aggregate measure is promising. However, it will have to go through refinements and adjustments to be the different school administrators. The development of model relating the productivity index with a capability index is suggested as the most interesting extension of the model.
Thesis (M.S. Industrial Engineering)--University of the Philippines, Diliman.
Typescript.
Keywords: Engineering schools -- Curricula. -- Philippines